An Empirical Study Of Profitability And Liquidity On Price Earning Ratio In Banking Companies Listed On Idx For The Period 2020 – 2022 - Fitria Haquei; Elis Badariah; Imat Hikmat; Bambang Hermawan; Didit Haryadi (Desanta Publisher, 2024)
This research aims to investigate the interaction between return on assets, current ratio, and price earning ratio in Indonesia's banking sector. The objective is to gain insight into how these factors interact and affect the price-earning ratio of companies in Indonesia's banking industry. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of banking sector companies in Indonesia operating in Indonesia as many as 46 companies; with purposive sampling technique, the authors get a sample of 30 companies from 2020 - 2022. This study examines the relationship between return on asset profitability, liquidity current ratio and price earning ratio through statistical analysis and linear regression modelling techniques with SPSS version 26. The results showed that the return on assets hurts the earning ratio. Liquidity current ratio does not significantly affect the price earning ratio; return on assets and current ratio do not have a considerable impact simultaneously on the price earning ratio. The findings contribute to the literature on corporate valuation by providing empirical evidence specific to the banking sector in Indonesia. This research provides implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive the earning ratio, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provides benefits in the context of financial management.